Ethnomathematics: Exploration at The Great Mosque of Demak - Muhammad Jamalul Huda (Institut Agama Islam Negeri Palopo, 2025)
Conceptual understanding of mathematics in elementary schools greatly influences students' problem-solving abilities. This study aims to find and describe the results of the exploration of ethnomathematics forms in the building of the Great Mosque of Demak, especially in the material of flat shapes. In addition, students can understand abstract mathematical concepts through concrete objects. This study is a descriptive qualitative study. Data collection techniques are by observation and documentation. The findings reveal that the structure of the Great Mosque of Demak contains rich elements of mathematical concepts, especially related to flat shapes such as triangles (seen in the shape of the roof structure), rectangles (visible in the windows and door frames), and circles (present in decorative motifs and ornaments). These geometric patterns not only reflect the cultural identity of the region but also offer meaningful contexts for introducing mathematical concepts in elementary school.